FOOD ENVIRONMENT OF JUNIOR HIGH SCHOOLS IN TOMOHON CITY, INDONESIA - Ishak Halim Octawijaya; Windy Mariane Virenia Wariki; Ai Hori; Masao Ichikawa (The Indonesian Journal of Public Health, 2022)
Introduction: In Indonesia, child obesity is increasing, and children take a substantial amount of daily calorie from food consumption at school. Methods: This paper describes school food environment in Tomohon City, North Sulawesi Province. We conducted on-site observation and interview with food vendors at 20 junior high schools, describing the food environment by availability and sales of foods and beverages at schools in urban and rural areas. Rice or noodle meals and deep-fried snacks were sold in all schools. Result: The availability and sales of industrial sweets and sugar-sweetened beverages were greater in urban than rural areas, whereas those of fruits were greater in rural areas. Oily and sugary foods and beverages are widely available and consumed by students at schools in the city of Indonesia. Conclusion: Such school food environments and dietary habits should be improved in the effort of halting the increasing prevalence of child obesity.